Water and climate change: a sign of war or a chance for cooperation? A comparative study between Central Asia and South America: Água e mudança climática: um indício de guerra ou chance para a cooperação? Um estudo comparado entre a Ásia central e a América do Sul - Magalhaes Teixeira, Barbara (Conjuntura internacional, 2018)
Different than the traditional body of work of this field that claims water scarcity leads to conflict, or to another line of research that claims water scarcity actually leads to cooperation; this article proposes a different causal mechanism that links the importance of the pattern of relations existing between countries prior to climate change and resource scarcity, to try to explain why water scarcity causes conflict in some cases and cooperation in others.